2005
DOI: 10.5897/ajb2005.000-3129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron and growth inhibitors on siderophores production by Pseudomonas fluorescens

Abstract: The ability of Pseudomonas to grow and to produce siderophores is dependent on the iron content and the type of carbon sources in the medium. Under conditions of low-iron concentration the Pseudomonas isolates studied produced yellow-green fluorescent iron-binding peptide siderophores and the biosynthesis of this siderophores was affected by several different environmental parameters. Four basal media, supplemented with different concentration of iron, were employed to study the effect of iron and different or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…King B was the best medium for obtaining the highest value of siderophore. Similarly Rachid and Ahmed (2005) found that king B medium is better than several other media. Many studies indicated siderophore production by several fungi such as Aspergillus terreus (Waqas et al, 2015), Aspergillus fumigatus (Haas, 2014), and Chaetostylum fresenii (Thieken and Winkelmann, 1992).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…King B was the best medium for obtaining the highest value of siderophore. Similarly Rachid and Ahmed (2005) found that king B medium is better than several other media. Many studies indicated siderophore production by several fungi such as Aspergillus terreus (Waqas et al, 2015), Aspergillus fumigatus (Haas, 2014), and Chaetostylum fresenii (Thieken and Winkelmann, 1992).…”
Section: Discussionmentioning
confidence: 91%
“…Four media were prepared to detect siderophore production by 65P and 9F strains including: King B medium consisting of glycerine 10 g/L, proteose-peptone 20 g/L, and MgSO4 1.5 g/L (de Villegas et al, 2002), glucose medium consisting of K 2 HPO 4 0.56 g/L, Glucose 10 g/L, urea 0.85 g/L, and Glutamic acid 1 g/L (de Villegas et al, 2002), citrate medium consisting of K 2 HP0 4 6.0 g/L, KH2P04 3.0 g/L, (NH 4 )2S0 4 1.0 g/L, MgS0 4 .7H 2 0 0.2 g/L, and citric acid 4.0 g/L (Meyer and Abdallah, 1978) and asparagine medium consisting of Asparagine 5 g/L, MgSO 4 0.1 g/L, and K 2 HPO 4 0.5 g/L (Rachid and Ahmed, 2005). The pH for all the media was adjusted to 7.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations have been made for Pseudomonas sp. strains by Sharma and Johri (2003) and for P. fluorescens by Djibaoui and Bensoltane (2005). In addition, cell growth and siderophore production were inversely proportional responses.…”
Section: Discussionmentioning
confidence: 96%
“…Results show that pyoverdine production was inversely related to Fe 3+ concentration, whereas growth was directly proportional to iron concentration (Meyer et al, 1978;Visca et al, 1992;Villegas et al, 2002;Manwar et al, 2004). Djibaoui and Bensoltane (2005) observed a complete decline of siderophore production with 200 µg/L of iron as threshold level. This fact reflects the iron requirement for microbiological cellular processes (Sayyed et al, 2005).…”
Section: +mentioning
confidence: 95%